Pengaruh Penilaian Kualitas Pinjaman dan Harga Saham pada Perusahaan Perbankan (Periode 2014 – 2016) - Susanto, Andik (JURNAL EKOMAKS : Jurnal Manajemen, Ekonomi Kreatif dan Bisnis, 2018)
The purpose of this study is to determine the effect of current and non-performing loans against stock prices of banking companies listed on the Indonesia Stock Exchange for the period of observation in 2014 until 2016. Bank Indonesia in its regulation provides criteria of loan collectibility into 4 kinds that is current, in special attention, substandard and loss or non performing loans. This study focuses only on the view of current loans and non performings loans. From linear regression result obtained positive influence from current lending to stock price increase and negative influence from non performings loans to stock price increase. From the results of simultaneous testing results obtained that the current loans and non performings loans affect stock price changes in banking companies observation period 2014 to 2016.